FIGURATIVE LANGUAGE IN THE ROOM OF MY LIFE’S POEM BY ANNE SEXTON AND STILL I RISE’S POEM BY MAYA ANGELOU - Ary Iswanto Wibowo; Ali Akbar (Center of Language and Cultural Studies [CLCS], 2017)
The aim of this research is to find out the usage of figurative language appear in The Room of My Life’s poem by Anne Sexton and Still I Rise’s poem by Maya Angelou. The study focused on kinds of figurative language that appeared in the poems. A descriptive qualitative method was used in this study. Data were gathered from each line of the poetry then figurative language were grounded.The results showed that the poems mostly used three kinds of figurative language: personification, simile, and metaphor. Personifications were more dominant than similes and metaphors in The Room of My Life and similes were more dominant than personifications and metaphors in Still I Rise.